Clinical practice guidelines for the treatment of odontogenic infection of the Peruvian Health Social Security (EsSalud) - Cornejo Salazar, José Luis (2022)
Introduction. This article summarizes the evidence-based recommendations of the clinical practice guide (CPG) for the treatment of patients with odontogenic infections (dentoalveolar abscess, facial cellulitis and cervicofacial abscess) in the Social Security of Health of Peru (EsSalud). Objective. To provide evidence-based clinical recommendations for the treatment of patients with odontogenic infections in EsSalud. Methods. A guideline development group (GEG) was formed that included dental surgeons, specialists, and methodologists. The GEG formulated four clinical questions to be answered in this CPG. We conducted systematic searches for systematic reviews and - when deemed relevant - primary studies in PubMed and CENTRAL during 2019. The evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice and the treatment flow chart. Finally, the CPG was approved with Resolution No. 067 – IETSI-ESSALUD-2020. Results. This CPG addressed four clinical questions, divided into two topics: pharmacological management and surgical management of odontogenic infections. Based on these questions, six strong recommendations were formulated, two conditional recommendations, 11 points of good clinical practice, and a flow chart. Conclusion. This article summarizes the methodology and evidence-based conclusions of the CPG for the treatment of odontogenic infections (dentoalveolar abscess, facial cellulitis and cervicofacial abscess) in EsSalud.